English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a(a – x) = b(b – x); solve for x

2006-11-14 05:31:57 · 9 answers · asked by rejavanation 2 in Science & Mathematics Mathematics

9 answers

if u meant make x the subjct then tis is how u wd go abt it.

a^2 - ax = b^2 - bx
ax-bx=a^2 - b^2
x(a-b)= a^2-b^2
x =(a^2-b^2)/(a-b)
x =[(a-b)(a+b)]/(a-b) (using difference of two squares)
x =a+b

2006-11-14 05:36:39 · answer #1 · answered by de bizzle 2 · 0 1

It's homework for you kid... not us. It is supposed to be worked upon and answered by you, not us. the reason these kinds of problems are given is that you learn to solve your own problems. So by asking the answer for your problem at yahoo answers, you are doing yourself a disservice . Try to solve it yourself, even you you fail then also you would feel good that atleast you tried. otherwise, if you copy the answer from this forum, I will make it a mission of my life to tell all your friends that you cheated.
And by the way, I am your teacher who gave you that homework. So stop sitting in front of your stupid computer and get back to doing what I had given you for homework. See you in school tomorrow, bye for now.....

2006-11-14 13:42:24 · answer #2 · answered by swapna 1 · 0 1

a(a – x) = b(b – x)

a^2 - ax = b^2 - bx
bx - ax = b^2 - a^2
x(b-a) = (b+a)(b-a)
x(b-a) - (b+a)(b-a) = 0
(b-a)(x - (b+a)) = 0

x = b+a,
or b=a (and x=any number)
Everyone else so far (8 other answers) has missed this last point. If b=a you cannot divide by b-a or a-b since this would entail dividing by 0!

2006-11-14 13:33:16 · answer #3 · answered by ʎɓʎzʎs 3 · 0 0

a^2-ax=b^2-bx

collecting all x terms to oneside,

bx-ax=b^2-a^2

ie x(b-a)=b^2-a^2=(b+a)(b-a) using (a+b)(a-b)=a^2-b^2

Now dividing the above equation through out by (b-a) we get
x= (b+a)

2006-11-14 13:43:13 · answer #4 · answered by Reema 2 · 0 1

a^2-ax=b^2-bx
a^2-b^2=ax-bx
(a-b)(a+b)=(a-b)x
divide both sides by a-b
a+b=x

2006-11-14 13:35:50 · answer #5 · answered by Dupinder jeet kaur k 2 · 0 1

Sorry didnt work on that when i was in school , alothough i did get a B

2006-11-14 13:34:42 · answer #6 · answered by Anonymous · 0 2

a^2-ax=b^2-bx
a^2-b^2=ax-bx
(a-b)(a+b)=x(a-b) since a^2-b^2=(a+b)(a-b)
a+b=x

2006-11-14 13:40:15 · answer #7 · answered by kawal 2 · 0 1

a(a-x)=b(b-x)
a^2-ax=b^2-bx
ax-bx=a^2-b^2
x =(a^2-b^2)/(a-b)
=a+b

i hope that this helps

2006-11-14 13:39:37 · answer #8 · answered by Anonymous · 0 1

a^2-ax=b^2-bx
a^2-b^2=ax-bx
a^2-b^2=x(a-b)
x=(a^2-b^2)/(a-b)

2006-11-14 13:40:14 · answer #9 · answered by alandicho 5 · 0 1

fedest.com, questions and answers